Development and Implementation of Evidence-Based Practice in Cancer Care: Challenges and Opportunities - Winnie K.W. So (Elsevier, 2016)
The cancer burden is a global problem, and oncology nurses should be accountable for delivering safe and effective cancer care and providing the best possible experience for patients. The development and application of evidence-based practice in cancer care is an effective strategy in achieving this goal; however, the journey in which such practice involves may encounter various challenges. In this article, the author discusses her own experience, successful and unsuccessful of such a journey. Both challenges and opportunities are identified, and suggestions put forward for making collaborative efforts.